Diagnostic Assessment In Identifying Learning Readiness Of Grade 1 Students At Elementary School Muhammadiyah Plus Batam - Titin Listiati; Sholehuddin (International Journal of Technology and Education Research, 2026)
The gap readiness Study student grade 1 school base is problematic crucial pedagogical, where diversity background behind education child age early, stimulation family, and maturity social-emotional create variation profile wide readiness, while practice assessment comprehensive and standardized diagnostics Not yet fully institutionalized in schools basic research This aim For explore carrying out diagnostic assessments in identify readiness Study student Grade 1 of Muhammadiyah Plus Elementary School Batam. Type research used is study qualitative with field research approach, involving two class teachers, two tens eight students and parents as data sources. Research results on non- cognitive dimensions show that student enter school with enthusiasm tall However accompanied by anxiety transitional significant, reinforcement - dependent motivation external, interest strong in activity kinesthetic However low on tasks academic structured, welfare varying psychological, as well as habit minimal learning outcomes limited stimulation structured at home. In the dimensions cognitive, identified gap wide in mastery letters, numbers, motor skills smooth, and understanding beginning core material for grade 1. Mapping readiness Study produce distribution two tens nine percent student category Ready, fifty percent Less Ready category, and two tens One percent Not Ready category. Obstacles Study main detected covering disturbance focus and attention short, readiness read low, readiness social limited, maturity motor fine not optimal, and difficulty regulations emotions. Implementation results study in the form of adoption practice assessment diagnostic integrated as policy mandatory at the beginning year teachings, teacher training in development multidimensional data instruments and interpretation, design learning differentiated based profile individual readiness, as well as development system mentoring involving teachers, friends peers, and parents.